Synthesis and Preliminary Kinetic Study of 5-fluorouracil Derivatives for Targeting Colon Tumor - Mohammed, Mohammed H.; Rahi, Firas Aziz; Naji, Hasanain Amer (JOURNAL OF ADVANCES IN CHEMISTRY, 2011)
5-Fluorouracil (5-FU) is used widely as an anticancer drug to treat solid cancers, such as colon, breast, rectal, and pancreatic cancers; although itâ€™s clinical application is greatly limited by its short plasma half-life, poor tumor affinity, myelosuppression, and gastrointestinal toxicity. To tackle these problems, numerous modifications of the 5- Fu structure have been performed.Thus, 5-Fu as possible colon specific prodrugs were synthesized in which 5-Fu is attached to amino acids (alanine & phenylalanine) using succinate group as a spacer via amide or ester bond. An approach to improve the properties of 5-fluorouracil is the chemical transformation into bioreversible derivatives (prodrugs) which are converted to the parent drug by enzymatic and / or chemical hydrolysis. The synthesis of the target compounds were accomplished following multistep reaction procedures, the chemical reaction followed up and the purity of the products were checked by TLC. Â Â The structures of the final compounds were confirmed by their melting points, infrared spectroscopy and 1H-NMR spectra. The hydrolysis of compounds III, IV, V, and VI in aqueous buffer solutions of pH 1.2 and pH 7.4 were studied. Â Â Compounds III, IV, V and VI had enough stability at pH 1.2 (t = 429.874min, t =429.874min, t=334.336min and t =376.139min respectively) and at pH 7.4 (t=601.823min, t=601.823min, t=429.874min and t=501.519min respectively); expecting that hydrolysis of these compounds by microbial enzymes in the colon will deliver 5-fluorouracil spontaneously.